TEXTUAL EQUIVALENCE IN THE TRANSLATION OF ENGLISH TEXTS INTO INDONESIAN - Triastika, Herlyn (IJLECR (International Journal of Language Education and Cultural Review), 2017)
This research aims to determine textual equivalence in the translation of scientific texts in English into Indonesian in depth. This study used a qualitative approach using the content analysis method. The data to the analysis performed in this study based on the six-step qualitative research developed by Myring. The findings in this study indicate that: (1) The equivalence of thematic structure contained in the translation of textbooks Approaches to Discourse into Indonesian is the equivalence on the pattern/ thematic arrangement of the unmarked theme and a simple theme/topical theme, (2) the information structure equivalence Between source text (ST) and target text (TT) is the equivalence in the form of organization of given and new information. (3) Equivalence in the cohesive devices translation is found in the use of grammatical cohesive devices, (4) The translation method used is the literal translation, (5) The discovered distortion was fully related to the aspects of semantics and linguistic equivalents, (6) The factors causing distortion are the translators’ skills and competencies, (7) The impact inflicted by the various distortion in the target text (TT) is that the translation readersgetdifferent messages from the message of source text (ST).